2022
DOI: 10.1038/s41598-022-23750-4
|View full text |Cite
|
Sign up to set email alerts
|

KLF15 suppresses tumor growth and metastasis in Triple-Negative Breast Cancer by downregulating CCL2 and CCL7

Abstract: Kruppel like factor 15 (KLF15), a transcriptional factor belonging to the Kruppel-like factor (KLF) family of genes, has recently been reported as a tumor suppressor gene in breast cancer. However, the specific mechanisms by which KLF15 inhibits BrCa have not been elucidated. Here we investigated the role and mechanism of KLF15 in triple-negative breast cancer (TNBC). KLF15 expression and methylation were detected by RT-qPCR, RT-PCR and methylation-specific PCR in breast cancer cell lines and tissues. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…We observe a significant, uniporter-dependent reduction in KLF15 protein levels in DP-expressing cells. Reduction in KLF15 levels has been correlated with tumor growth and poor prognosis in several types of cancer 61-66 , but to our knowledge, this is the first time KLF15 expression changes have been implicated in liver cancer. KLF15 also regulates genes associated with gluconeogenesis, lipogenesis, metabolism of non-BCAA amino acids, and the urea cycle 31,67,68 .…”
Section: Discussionmentioning
confidence: 83%
“…We observe a significant, uniporter-dependent reduction in KLF15 protein levels in DP-expressing cells. Reduction in KLF15 levels has been correlated with tumor growth and poor prognosis in several types of cancer 61-66 , but to our knowledge, this is the first time KLF15 expression changes have been implicated in liver cancer. KLF15 also regulates genes associated with gluconeogenesis, lipogenesis, metabolism of non-BCAA amino acids, and the urea cycle 31,67,68 .…”
Section: Discussionmentioning
confidence: 83%
“…For example, a study reported that tumor-associated macrophages secrete TGF-β1 to promote cancer stem cells and EMT in hepatocellular carcinoma(Fan et al 2014 ). Multiple studies have shown that CCL7 plays an important role in cancer metastasis, such as promoting the metastasis of breast cancer(Kanyomse et al 2022 ), colorectal cancer(Xu et al 2022a , b ), gastric cancer(Chen et al 2020 ) and other tumors. In particular, cancer-associated fibroblasts in HCC tumor tissue can secrete CCL7 to promote HCC metastasis(Liu et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4b reports the following 12 genes obtained from the PPI network: ACTG2, PRKAR2B, ALDH2, PRKACB, KRT19, KRT18, WASF3, DLG5, TRIM37, GSTM3, GSTA1, and CYP2A6. Four genes (KRT18, KRT19, PLCB4, and PRKACB) were related to the estrogen signaling pathway, which is reported to play a key role in breast cancer progression and treatment [66][67][68]. Three genes (CYP2A6, GSTA1, and GSTM3) were linked to chemical carcinogenesis-the DNA adduct pathway-involved in cancer development [69,70].…”
Section: Dataset2mentioning
confidence: 99%